Estimation of Daily Life Time Series Data Affected by Rainfall - Hochin, Teruhisa; Nomiya, Hiroki (International Journal of Engineering and Technology, 2018)
The amount of sewage flow, which is one of daily life data, was estimated for their efficient management. The amounts of flow of a typical day were tried to be adjusted to those of a day. The values for the adjustment were tried to be estimated by using the multiple regression analysis. This method is applied to the estimation of the ammonia nitrogen concentration, which is the major factor of the quality of sewage flow. The estimation results show that this method is applicable to the estimation of the ammonia nitrogen concentration, and that the amount of rainfall is dominant in estimating the ammonia nitrogen concentration.Â